2014
DOI: 10.1063/1.4859256
|View full text |Cite
|
Sign up to set email alerts
|

Communication: Permanent dipoles contribute to electric polarization in chiral NMR spectra

Abstract: Nuclear magnetic resonance spectroscopy is blind to chirality because the spectra of a molecule and its mirror image are identical unless the environment is chiral. However, precessing nuclear magnetic moments in chiral molecules in a strong magnetic field induce an electric polarization through the nuclear magnetic shielding polarizability. This effect is equal and opposite for a molecule and its mirror image but is small and has not yet been observed. It is shown that the permanent electric dipole moment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
49
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 14 publications
1
49
0
Order By: Relevance
“…The results of computations of σ (1) and P/kT (Buckingham, 2014;Buckingham et al 2015) give hope that NMR experiments will soon provide chiral discrimination as in other forms of spectroscopy. Estimates of alternating voltages of the order of 1 nV for signals from protons in pure chiral liquids (Buckingham & Fischer, 2006) increase to 1 μV and substantially higher for heavier nuclei because of the dominance of P/kT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of computations of σ (1) and P/kT (Buckingham, 2014;Buckingham et al 2015) give hope that NMR experiments will soon provide chiral discrimination as in other forms of spectroscopy. Estimates of alternating voltages of the order of 1 nV for signals from protons in pure chiral liquids (Buckingham & Fischer, 2006) increase to 1 μV and substantially higher for heavier nuclei because of the dominance of P/kT.…”
Section: Discussionmentioning
confidence: 99%
“…Computations of σ (1)(N) (Buckingham & Fischer, 2006;Lazzeretti et al 2008;Monaco & Zanasi 2011;Pelloni et al 2013;Zanasi et al 2007) have shown that its contribution to the electric polarization is likely to be too small for easy detection, even for heavier nuclei such as 13 C and 19 F. However, a recent Communication (Buckingham, 2014) showed that there is an additional contribution to the rotating polarization in the case of dipolar molecules; the permanent electric dipole moment μ (0) contributes a temperature-dependent orientation polarization through the torque exerted on the dipole by the precessing nuclear magnetic moment through the antisymmetric part of σ (N) αβ . The molecular properties that give the rotating electric polarization associated with precessing nuclear spins following a π/2 pulse are σ (1)(N) + P (N) /kT, where k is the Boltzmann constant, T the absolute temperature, and the pseudoscalar P (N) for nucleus N is (a repeated Greek suffix implies a sum over all three Cartesian components)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the induced P is always oriented along B × m I (thus rotating with m I ), points in opposite directions for the two enantiomers (hence its chirality-sensitivity), and is proportional to the pseudoscalar σ (1) , isotropic average of a third-rank tensor σ ijk (i, j, k = x, y, z) known as shielding polarizability [3, 5,10]. However, computational estimates of σ (1) in diamagnetic molecules suggest that it is generally too small to be detected [9,11,12].In this Letter we propose a theory of paramagnetic NMR chiral discrimination which is valid for molecules with a ground state of arbitrary degeneracy. We describe the response of the degenerate system in terms of a generalized shielding polarizability tensor Φ ijk defined by analytical third-derivatives of the free energy, reducing to σ ijk in the limit of a non-degenerate ground state.…”
mentioning
confidence: 99%
“…Here σ is the nuclear shielding constant, the isotropic average of the shielding tensor σ describing the departure from B of the local magnetic field at nucleus I due to surrounding electrons. The coherent in-plane precession of m I gives rise to a free-induction decay (FID) signal picked up by a coil with axis in the xy-plane, whose Fourier transform provides the NMR spectrum.The combined effect of B and m I on the electrons of a diamagnetic molecule has been shown to induce an electric dipole polarization [3, 5,9], which can be obtained by expanding the energy of the molecule W (E, B, m I ) ≡ W in a power series of B, m I , and an external electric field E, thermally averaged over all molecular orientations in the presence of B and m I [9]. Truncation of the ensuing power series to leading order in the inducing fields yields the average induced polarization P i ≡ P d,i as [3, 5,9]:…”
mentioning
confidence: 99%